Pembuatan Arsitektur Aplikasi Di Perusahaan Transportasi XYZ Menggunakan Metode Enterprise Architecture Planning (EAP) - Merlin Merlin; Adi Wibowo; Lily Puspa Dewi (Jurnal Infra, 2016)
Transportation company XYZ is a company engaged in bus-based transport services. Most of the company’s business processes are done manually and don’t have any integrated information system. The company has a program created by a freelance programm, but the program’s features are still incompletes. Thus the analysis and design of enterprise architecture using Enterprise Architecture metod (EAP) are needed for the transportation company XYZ. The first process is analyze the business model and business strategy of the company. After that, identification process to know what information technology that company has, its problems, and company’s needs ini the present and in the future. After all information are gathered then design of data architecture, aplication architecture, and technology architecture process were conducted.